2014
DOI: 10.2147/dddt.s75565
|View full text |Cite
|
Sign up to set email alerts
|

A thorough QT study in the context of an uptitration regimen with selexipag, a selective oral prostacyclin receptor agonist

Abstract: The effects of selexipag and its active metabolite ACT-333679 on cardiac repolarization were assessed in a thorough QT study as per International Conference on Harmonisation E14 guidance. In this randomized, double-blind, placebo/positive-controlled, parallel-group study, healthy male and female subjects were randomized to receive escalating doses of selexipag (n=91) or placebo/moxifloxacin (n=68). Ascending multiple doses of selexipag in the range of 400–1,600 μg or placebo were administered twice daily for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Both compounds demonstrated high binding affinity toward human albumin and α‐acid glycoprotein. The plasma protein binding is more than 99% for both compounds, and there was no absolute saturation level of binding in the clinically relevant concentration range . This selectivity for the IP receptors prevents dose‐related side effects such as nausea and vomiting that might result from activation of the other prostanoid receptors .…”
Section: Epidemiology Of Pahmentioning
confidence: 96%
See 2 more Smart Citations
“…Both compounds demonstrated high binding affinity toward human albumin and α‐acid glycoprotein. The plasma protein binding is more than 99% for both compounds, and there was no absolute saturation level of binding in the clinically relevant concentration range . This selectivity for the IP receptors prevents dose‐related side effects such as nausea and vomiting that might result from activation of the other prostanoid receptors .…”
Section: Epidemiology Of Pahmentioning
confidence: 96%
“…Another major potential side effect of every drug is drug‐induced QT interval prolongation, which invariably increases the risk of torsades de pointes and resultant sudden cardiac death. As per the International Conference on Harmonisation E14 guidance, the effects of selexipag and its active metabolite ACT‐333679 on cardiac repolarization were evaluated compared to a positive control (moxifloxacin) in a QT study . They used the 800‐mg and 1600‐mg drug dose as they were employed in the GRIPHON Study and found that the exposure‐response analysis did not show a pertinent relationship between plasma concentrations of selexipag or ACT‐333679 and QTc, and they concluded that selexipag did not have any significant effect on cardiac repolarization.…”
Section: Epidemiology Of Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…Food had no significant effect on exposure to selexipag and ACT-333679, but it decreased the rate of absorption, as shown by a decrease in C max and a delay in the median time to reach maximum plasma/blood concentration (t max ) of 1-1.5 h. The observed increase in exposure of 10 % for selexipag and decrease of 27 % for ACT-333679 is within the pharmacokinetic variability of the compound, which should also be viewed in the light of the low dose administered, in the microgram range [5,6,8]. Also relevant in this context is that in clinical practice, selexipag is used at an individualized dose of 200-1600 lg bid, reached after weekly up-titration [9].…”
mentioning
confidence: 90%
“…However, the single-dose data for both selexipag and ACT-333679 showed a dose-proportional increase in both exposure variables across the dose range tested, from 100 to 800 lg [2]. Gradual up-titration to an individual patient's highest tolerated dose is the generally accepted regimen for IP receptor agonists [3], which has now been extensively studied in healthy subjects up to 1800 lg twice daily (bid) as well as in patients up to 1600 lg bid [4][5][6][7]. The pharmacokinetics of selexipag were dose proportional across the entire dose range following multiple doses, as evidenced by the point estimate of the population mean slope for area under the plasma concentration-time curve during a dose interval (AUC s ) and maximum plasma concentration (C max ) [5].…”
mentioning
confidence: 99%